EU Integrated Urban Initiatives Policy Learning and Quality of Life Impacts in Spain - Navarro Yáñez, Clemente J.; Rodríguez-García, María Jesús; Guerrero-Mayo, María José (Springer Nature, 2023)
This open access book presents a unique interdiscplinary analysis of urban projects promoted by the EU from a comparative perspective This book presents cross-sectional and cross-time analyses at the territorial level targeted by these initiatives focusing on the design, theory and impacts of urban projects developed under the framework of initiatives promoted by the European Union. The book includes a new methodology to analyse the design and theory of urban plans (the comparative urban portfolio analysis) and quasi-experimental strategies to perform impact assessment at the neighbourhood level (the territorial target of those initiatives). Although empirical analyses focus on examples in Spain, the resulting analytical and methodological outcomes of these studies can be applied in a broader context to analyse integral urban policies in other countries.